Rheological analysis of water clay compositions in order to investigate mudflows developing in canals - Geraldo De, F. Maciel; Dos Santos, Hamilton Kiryu; Fabiana De, O. Ferreira [UNESP] (My University, 2009)
This paper describes the physical and rheological property mixtures of water and kaolinitic clay that form the interstitial fluid found in muds from inundations or torrential lava. Several compositions with varying volume concentrations (Cv) were tested in a highprecision R/S rheometer (shear rate x shear stress). The rheometric parameters such as critical stress, apparent viscosity and outflow curves were established. A detailed analysis of the possible thixotropic fluid (shear thinning) and preparation of the mixtures were carried out. Such mud-type mixtures were well adjusted to the Herschel-Bulkley rheologic model at 03 parameters namely τ = n τ =τ c + Kγ , where τ is the shear stress; τc the yield stress (or initial rigidity); k is the consistency term; n the flow index; and γ& = du dy the deformation rate or shear rates. Considering that this is a thorough research that seeks to infer laws of friction on a canal taking into account the non- Newtonian rheology of the flowing material, it is observed that the tested mixtures specifically keep away from the Newton model, though less for the Bingham model, and adjusted well to the Herschel-Bulkley model, especially for lower deformation rates. Finally, from a refined literature review on the subject, it was appropriate to describe in detail a wider range of deformation rates and overall behavior laws of the various parameters of the Herschel Bulkley as a function of the concentration by volume (Cv). © 2009 by ABCM.
Keywords: Herschel-Bulkley; Mud; Non-newtonian fluid; Rheology